DETERMINAN PERTUMBUHAN PENYALURAN KREDIT MODAL KERJA DI BANK KBMI 4 PADA TAHUN 2011-2021 - Murti, Chandra; Hasta Dwi Pradana; Jaka Sanjaya (Media Ekonomi, 2024)
The purpose of this study is to analyze the influence of Non-Performing Loan, third-party funds, Net Interest Margin, and Gross Domestic Product per capita on the growth of working capital loan banks in KBMI category 4 period 2011-2021. This research employs secondary data acquired from banks in the Buku Empat Category between 2011 and 2021. To analyze the data, a panel data regression model was utilized, with eviews13 serving as the research instrument. The findings of this study show that net interest margin and third-party funds have a positive and statistically significant impact on Working Capital Loan growth. Additionally, this study demonstrates that the mandatory reserve requirement (GWM) significantly and negatively impacts Working Capital Loan growth. In contrast, neither the unemployment rate nor the GDP per capita have a substantial impact on KMK growth.